Development and Evaluation of New Air (Automated Meter Reading) System : A Case in PT.PLN (Persero) Distribution Jakarta Raya and Tangerang - Sari, Hendriana Mayang; Firman, Aries F (The Indonesian Journal of Business Administration, 2015)
Abstract.Â Automated Meter Reading (AMR) is technology used in electricity meter that able to monitor the customerâ€™s electricity usage remotely. DMR or Data Monitoring Report is the feature in existing AMR system which function is to analyze the load profile data from meters. Load profile data is a powerful database to analyze customer's electricity usage, but due to the difficulty of operating and less friendly user interface, it was only used for billing purposes. With this system, the data analysis harder to be done because need to consolidate data from 9 (nine) locations manually, and the success of load profile data downloaded also not well monitored. Started from those problems, came the idea to develop new Data Management Report System as Business Process Improvement (BPI) that expected to be able to close the â€œholes.â€ The new system called MONAS (Monitoring dan Analisa AMR Sistem).Â The objective of this research is to develop new Data Monitoring Report for AMR System as the business solution and assess the performance of new system in several parameters: productivity, cost, time and quality. This research methodology utilizes quantitative with purposive sampling technique which object the employees of Disjaya categorized in a4 types: active user, passive user, management and system developer. The objective of survey is to dig in the userâ€™s perspective about the performance improvement as the impact of MONAS implementation. Next, to get to know either our organization is already done BPI, it needs to be compared. This research compares the previous performance with the current and the current performance with the other benchmarked company.Â As the result, MONAS succeed to improve : productivity (to 13.75 times), cost (to 26 times more efficient), time (to 23 times faster) and quality (29.78% better than previous system). MONAS also succeed to answer the problems by increasing the success rate of load profile data. Having higher percentage of load profile data downloaded combined with complex calculation, could enhance the finding of electricity usage abnormalities. As recommendation, MONAS needs to be enhanced in features to increase response time, capital capacity (server) should be ready with more number of customers and prepare MONAS to be implemented in national scale.Â Keywords: Automated Meter Reading (AMR), Business Process Improvement (BPI), MONAS (Monitoring danAnalisa AMR Sistem)Â